Perbandingan Sistem Pelayanan Kesehatan Di Indonesia Dan Di Singapura - Nisa, Karina Fachrun; Dompak, Timbul; Lodan, Karol Teovani (LPPM Universitas Putera Batam, 2024)
The health service system is a vital aspect in ensuring the welfare of society. In the context of Indonesia and Singapore, the two countries have different approaches to providing health services. This comparative study aims to analyze the significant differences between the health care systems in the two countries. Indonesia, as a developing country with a large population, faces challenges in providing equitable access to health for its entire population. Indonesia's health system is based on the principle of mutual cooperation, where the central and regional governments play a role in providing health services. However, obstacles such as lack of infrastructure, limited human resources, and disparities between urban and rural areas are still major problems. On the other hand, Singapore is known for its efficient and quality health system. With a more centralized approach and supported by advanced technology, Singapore has achieved excellent health outcomes at relatively low costs. A mandatory health insurance system and widespread adoption of information technology have enabled Singapore to provide affordable, high-quality health services to its entire population. This study will compare several key aspects of the two health systems, including accessibility, quality of service, cost efficiency, and level of community satisfaction. Through this comparative analysis, it is hoped that valuable lessons can be found that can help develop the health systems in both countries and encourage improvements in the welfare of society as a whole.